A Case of Complete Renal Duplex with H-Shaped Ureter - A. Ghobashy; M. El-Shazly; A. Lari; O. Al-Hunaidy; A. Allam; N. Alenezy; E. Yordanov; B. Hathout (Case Reports in Urology)
We present a case of complete renal duplex with H-shaped double ureter opening into the bladder with 2 separate orifices. It is an extremely rare variety of renal duplex which was reported only once in the literature. Fifty-four-year-old male presented to our department with right renal pain. Noncontrast CT revealed stone midthird right ureter with duplex right kidney. Retrograde ureteropyelography and ureteroscopy revealed this rare anomaly.